The influence of corporate governance on tax avoidance and earning management - Syafa’at, Hilal; Dinarjito, Agung (Educoretax, 2025)
The agency relationship between company owners and company managers raises potential problems between the two due to conflicts of interest. Several issues that reflect agency problems include tax avoidance and earnings management, the aim of which is to provide profits for managers. One tool to prevent tax avoidance and earnings management is good corporate governance. This research aims to analyze the influence of corporate governance in reducing tax avoidance and earnings management. The research method used is descriptive qualitative research approach systematic literature review (SLR) uses framework PRISMA. The references used come from articles published from 2014 to 2024 with a focus on companies in Indonesia. Based on the results of the literature review, there is a tendency that corporate governance can reduce the incidence of tax avoidance and earnings management. However, there are several studies that present the opposite results. This research aims to enhance our understanding of governance studies concerning tax avoidance and earnings management. In addition, we hope this research will highlight the significance of implementing good corporate governance for companies.